Genetic variants in PNPLA3 and TM6SF2 predispose to the development of hepatocellular carcinoma in individuals with alcohol‐related cirrhosis. (October 2018) - Stickel, Felix; Buch, Stephan; Nischalke, Hans Dieter; Weiss, Karl Heinz; Gotthardt, Daniel; Fischer, Janett; Rosendahl, Jonas; Marot, Astrid; Elamly, Mona; Casper, Markus; Lammert, Frank; McQuillin, Andrew; et al.
Abstract : OBJECTIVES: Variants in patatin‐like phospholipase domain‐containing 3 ( PNPLA3; rs738409), transmembrane 6 superfamily member 2 ( TM6SF2; rs58542926), and membrane bound O‐acyltransferase domain containing 7 ( MBOAT7; rs641738) are risk factors for the development of alcohol‐related cirrhosis. Within this population, PNPLA3 rs738409 is also an established risk factor for the development of hepatocellular carcinoma (HCC). The aim of this study was to explore possible risk associations of TM6SF2 rs58542926 and MBOAT7 rs641738 with HCC. METHODS: Risk variants in PNPLA3, TM6SF2, and MBOAT7 were genotyped in 751 cases with alcohol‐related cirrhosis and HCC and in 1165 controls with alcohol‐related cirrhosis without HCC. Association with the risk of developing HCC was analyzed using multivariate logistic regression. RESULTS: The development of HCC was independently associated with PNPLA3 rs738409 (ORadjusted 1.84 [95% CI 1.55‐2.18], p = 1.85 × 10‐12) and TM6SF2 rs58542926 (ORadjusted 1.66 [1.30‐2.13], p = 5.13 × 10‐05), using an additive model, and controlling the sex, age, body mass index, and type 2 diabetes mellitus; the risk associated with carriage of MBOAT7 rs641738 (ORadjusted 1.04 [0.88‐1.24], p = 0.61) was not significant. The population‐attributable fractions were 43.5% for PNPLA3 rs738409, 11.5% for TM6SF2 rs58542926, and 49.9% for the carriage of both the variants combined. CONCLUSIONS: Carriage of TM6SF2 rs58542926 is an additional risk factor for the development of HCC in people with alcohol‐related cirrhosis. Carriage of both PNPLA3 rs738409 and TM6SF2 rs58542926 accounts for half of the attributable risk for HCC in this population. Genotyping will allow for more precise HCC risk‐stratification of patients with alcohol‐related cirrhosis, and genotype‐guided screening algorithms would optimize patient care.